Comparison accuracy between standalone global navigation satellite system [GNSS] and differential global navigation satellite system [DGNSS] in hydrography surveying / Muhammad Hafiz A Aziz - A Aziz, Muhammad Hafiz (2019)
Positioning plays a greater role in determining the accurate and precision of the target in hydrographic surveying. There are several methods for observation technique to obtain position in Global Navigation Satellite System (GNSS) surveying. Many factors can affect the accuracy and precision of the target between Standalone Global Positioning System and JUPEM Differential Global Positioning System. Thus, purpose of this study is to compare the accuracy of Standalone GNSS and JUPEM DGNSS in hydrographic surveying. The achievable accuracy will be determined either the capabilities of Standalone GNSS and JUPEM DGNSS are in line with IHO standard accuracy to special order, first order and second order which is 2m level. In order to determine the accuracy of both Standalone GNSS and JUPEM DGNSS, a single sounding line has been created on the ground at study area using RTK method. After that, the sounding line will be observed using Standalone GNSS and JUPEM DGNSS separately due to the limitations of the instrument and it cannot be done simultaneously. A trolley will be used to imitate the motion of a boat but the speed is very slow compare to the normal speed of a boat for hydrographic surveying. The data that has been obtain will be process in multiple software such as AutoCad for filtering and Microsoft Excel for calculating the residual and RMSE to determine the accuracy for each of the method. As a result, the accuracy of the standalone GNSS and JUPEM DGNSS are in line with the accuracy provided by IHO which is below two meter accuracy. From the research, the horizontal accuracy of JUPEM DGNSS positions is in the range of one meter to two meter. With this range of accuracy, it is suitable for hydrographic positioning utilize the JUPEM DGNSS services more effectively. As for further research, both of the method should been done simultaneously on the water areas using a boat like actual job in hydrographic surveying.